Purple Pearl Travel and Tours Agency / Khairool Izwan Jamil ... [et al.] - Jamil, Khairool Izwan; Sidek, Sukri; Ab.Halim, Muhammad Yusoff; Zahri, Mohd Amiri; Mutahal, Abdul Malik (Faculty of Civil Engineering, 2004)
Purple Pearl Travel and Tours Agency is travel agency which is a based in Malaysia and wholly owned by bumiputera. We provide tourism packages in our nice country. After some discussions,an agreement has been made among the five shareholders. The business has been planned properly and approximately it took about two and a half years for our business to commence.